Daya Bunuh Ekstrak Air Daun Salam (Syzygium polyanthum) terhadap Larva Aedes sp - Ratih Dewi Dwiyanti; Rion Dediq; Anny Thuraidah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2017)
edes sp is known as a mosquito that transmits various diseases. In addition to spreading dengue fever and chikungunya, these mosquitoes also spread the virus zika is quite dangerous. One of the effort to controlling these diseases is to eradicate the vector by using materials that can be taken from plants one of them is bay leaf (Syzygium polyanthum). The purpose of this study is to determine the kills power of Syzygium polyanthum water extract against Aedes sp larvae. This research uses true experiment with Posttest Only With Control Group Design design. Data were obtained from the number of larval deaths in the Syzygium polyanthum extract in each control group and treatment group for 24 hours. The results showed that the percentage of bayleaf water extract which has the largest number of larval deaths was at 32% concentration with 55% death percentage. It was concluded that each concentration of aqueous bay leaf water extract given had a killing power against Aedes sp larvae with the lowest percentage of 2.5% and the highest 55%. Based on the result of Kruskal-Wallis test showed that water extract of the bay leaf was able to kill Aedes sp larvae at each treatment with the value of sig 0,001. Suggestion for the next researcher to test the power of killing the water extract of Syzygium polyanthum to Aedes sp larvae by increasing the concentration of salted bay water extract.